Penegakan Dan Perlindungan Hak Asasi Manusia Bagi Korban Malpraktik di Indonesia - Daeng, Yusuf; Milthree Saragih, Geofani (Jurnal Hukum Non Diskriminatif, 2023)
Malpractice is one of the most central issues related to health law and health care. Medical law or health law is a relatively young branch of science in Indonesia. The newly developed medical law and the newly recognized concept of malpractice are in contrast to the many attentions on health law, especially on doctors and hospitals. So this problem is how the rights of patients and patients' families in obtaining medical records, how to resolve disputes between patients and their families with the defendants and how the level of settlement of the legal process in malpractice cases is. From these problems, this paper aims to answer problems regarding medical disputes why patients and their families have difficulty in realizing their right to obtain medical records. That in proving malpractice cases it is difficult to prove, because it is difficult to obtain the contents of medical records, for patients who are affected by malpractice cases.